Polychaeta Orbiniidae from Antarctica, the Southern Ocean, the Abyssal Pacific Ocean, and off South America - Blake, James A. (Zootaxa, 2017)
The orbiniid polychaetes chiefly from Antarctic and subantarctic seas and off South America are described based on collections of the National Museum of Natural History and new material from surveys conducted by the United States Antarctic Program and other federal and privately funded sources as well as participation in international programs. A total of 44 species of Orbiniidae distributed in 10 genera are reported from the Pacific Ocean and waters off South America and Antarctica. Twenty-one species are new to science; one species is renamed. Berkeleyia heroae n. sp., B. abyssala n. sp., B. weddellia n. sp.; B. hadala n. sp., Leitoscoloplos simplex n. sp., L. plataensis n. sp., L. nasus n. sp., L. eltaninae n. sp., L. phyllobranchus n. sp., L. rankini n. sp., Scoloplos bathytatus n. sp., S. suroestense n. sp., Leodamas hyphalos n. sp., L. maciolekae n. sp., L. perissobranchiatus n. sp., Califia bilamellata n. sp., Orbinia orensanzi n. sp., Naineris antarctica n. sp., N. argentiniensis n. sp., Orbiniella spinosa n. sp., and O. landrumae n. sp. are new to science. A new name, Naineris furcillata, replaces N. chilensis Carrasco, 1977, a junior homonym of N. dendtritica chilensis Hartmann‑Schröder, 1965, which is raised to full species status. Leodamas cochleatus (Ehlers, 1900) is removed from synonymy and redescribed. A neotype is established for Leodamas verax Kinberg, 1966, the type species. A general overview of Leodamas species is provided. The Leitoscoloplos kerguelensis (McIntosh, 1885) complex is reviewed and partially revised. Definitions of the genera of the Orbiniidae are updated to conform to recently described taxa. Several new synonymies are proposed following a reexamination of previously described type specimens. The morphological characters used to identify and classify orbiniids are reviewed. The biogeographic and bathymetric distributions of the South American and Southern Ocean orbiniid fauna are reviewed.